Effects of dietary amylose to amylopectin ratio on growth performance, carcass quality characteristics and meat fatty acids in Chinese Qinchuan cattle - Min-yu PIAO; Feng-ming HU; Fan-lin KONG; Yun-long LIU; Shuo WANG; Kai CUI; Tao SUN; Qi-yu DIAO; Yan TU (Journal of Integrative Agriculture, 2021)
This study evaluated the effects of the dietary starch amylose/amylopectin ratio on growth performance, rumen fermentation and blood parameters, carcass characteristics and marbling score, and meat fatty acid profiles and transcriptional changes in the genes involved in the gluconeogenesis pathway in Chinese Qinchuan cattle. Forty-five cattle were randomly divided into three groups. The bulls were fed a control diet (middle amylose/amylopectin ratio=0.47) or diets with either waxy corn starch (WS) inclusion (low amylose/amylopectin ratio=0.23) or pea starch (PS) inclusion (high amylose/amylopectin ratio=0.60) for 90 days. The bulls were individually allowed to receive the diets at the daily amount of at least 2.1% of their individual BW twice daily. The bulls were weighed at 45-day intervals, and blood and rumen fluid samples were also collected at 45-day intervals. The bulls were slaughtered and longissimus thoracis (LT) samples were collected for meat quality measurements. Compared with PS, the average daily gain (ADG) and feed efficiency in control and WS were increased (P<0.05) during d 0 to 45. However, the feed efficiency in PS was increased (P<0.05) compared with the control and WS during d 46 to 90. During the whole feeding trial, the ADG in control and WS showed trends that were higher (0.05<P<0.1) than that of PS, while other growth performance measures and feed intake did not differ (P>0.05) among the three groups. Compared with PS, the serum insulin concentration in WS was increased (P<0.05) at d 45, but not at d 90. Compared with control and WS, the serum SOD and T-AOC concentrations in PS were increased (P<0.05) at d 45, but not at d 90. Compared with control, the rumen microbial crude protein contents in WS and PS were increased (P<0.05) at d 0, while those of control and WS were higher (P<0.05) than that of PS at d 45, but not at d 90. Compared with PS, the backfat thickness in control and WS were increased (P<0.05), however, the marbling score and expression of genes related to the gluconeogenesis pathway in liver of the three groups did not differ (P>0.05). Chemical and physio-chemical compositions of LT did not differ (P>0.05) among the three groups. In conclusion, diets with low or middle amylose/amylopectin ratios increased the backfat thickness, and tended to improve ADG, but had no effect on other carcass characteristics, fat content in the LT, or the expression of hepatic genes related to the gluconeogenesis pathway in Chinese Qinchuan cattle.